Alcoholic Photoinitiated Polymerization-Induced Self-Assembly (Photo-PISA): A Fast Route toward Poly(isobornyl acrylate)-Based Diblock Copolymer Nano-Objects - Tan, Jianbo; Huang, Chundong; Liu, Dongdong; Zhang, Xuechao; Bai, Yuhao; Zhang, Li (ACS macro letters, 2016)
We report a fast alcoholic photoinitiated polymerization-induced self-assembly (photo-PISA) formulation via photoinitiated RAFT dispersion polymerization of isobornyl acrylate (IBOA) in an ethanol/water mixture at 40 °C using a monomethoxy poly(ethylene glycol) (mPEG) based chain transfer agent. Polymerization proceeded rapidly via the exposure to visible light irradiation (405 nm, 0.5 mW/cm2), and high monomer conversion (>95%) was achieved within 30 min. Kinetic studies confirmed that good control was maintained during the photo-PISA process, and the polymerization can be activated or deactivated by light. Finally, we demonstrated that a diverse set of complex morphologies (spheres, worms, or vesicles) could be achieved by varying reaction parameters, and a phase diagram was constructed.